2010
DOI: 10.3346/jkms.2010.25.10.1499
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Histologic Changes After Repeated Transcranial Direct Current Stimulation in Rat Stroke Model

Abstract: Transcranial direct current stimulation (tDCS) is associated with enhancement or weakening of the NMDA receptor activity and change of the cortical blood flow. Therefore, repeated tDCS of the brain with cerebrovascular injury will induce the functional and histologic changes. Sixty-one Sprague-Dawley rats with cerebrovascular injury were used. Twenty rats died during the experimental course. The 41 rats that survived were allocated to the exercise group, the anodal stimulation group, the cathodal stimulation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 28 publications
6
66
0
1
Order By: Relevance
“…Furthermore, similar results were 78 found and even maintained for at least 4 weeks after repetitive 79 anodal tDCS (Boggio et al, 2012). Beyond human, one study based 80 on AD rats suggested the application of anodal tDCS over the fron-81 tal cortex has beneficial effects on restoration of cognitive skill (Yu,82 Park, & Sim, 2014) which possibly resulted from the potential 83 neuron-protective effect (Kim et al, 2010) and the wide-spread 84 modulatory function in cortical-subcortical network of tDCS 85 (Fregni et al, 2006). 86 The stimulation parameters, such as polarity, stimulation time 87 and current intensity have diverse influences on the effects 88 induced by tDCS (Nitsche et al, 2008).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, similar results were 78 found and even maintained for at least 4 weeks after repetitive 79 anodal tDCS (Boggio et al, 2012). Beyond human, one study based 80 on AD rats suggested the application of anodal tDCS over the fron-81 tal cortex has beneficial effects on restoration of cognitive skill (Yu,82 Park, & Sim, 2014) which possibly resulted from the potential 83 neuron-protective effect (Kim et al, 2010) and the wide-spread 84 modulatory function in cortical-subcortical network of tDCS 85 (Fregni et al, 2006). 86 The stimulation parameters, such as polarity, stimulation time 87 and current intensity have diverse influences on the effects 88 induced by tDCS (Nitsche et al, 2008).…”
supporting
confidence: 65%
“…Based on previous findings, 89 it is commonly agreed that tDCS induced effects are modulated in a 90 polarity-specific manner ( (Benninger et al, 2010;Boggio et al, 2007). In rats, 103 repetitive rather than single tDCS has been proven to improve 104 motor function, and elicit inflammatory and regenerative pro-105 cesses in rat stroke models (Kim et al, 2010;Rueger et al, 2012). 106 Similar repetitive stimulations were found to have antiepileptic 107 effects in epilepticus rats (Kamida et al, 2011).…”
mentioning
confidence: 97%
“…Similarly, Kim et al (2010) found that neuronal axons at the internal capsule of infarcted hemispheres were better preserved after anodal TDCS stimulation in the rat stroke model.…”
Section: Discussionmentioning
confidence: 92%
“…Rats received TDCS daily until sacrifice. The TDCS parameters were set as follows: frequency, 10 Hz; intensity, 0.1 mA (Kim et al, 2010). The active electrode was positioned 5 mm to the left and 2 mm in front of the interaural line.…”
Section: Tdcs Therapymentioning
confidence: 99%
See 1 more Smart Citation